Platelet Ice Under Arctic Pack Ice in Winter. Issue 16 (20th August 2020) - Katlein, Christian; Mohrholz, Volker; Sheikin, Igor; Itkin, Polona; Divine, Dmitry V.; Stroeve, Julienne; Jutila, Arttu; Krampe, Daniela; Shimanchuk, Egor; Raphael, Ian; Rabe, Benjamin; Kuznetov, Ivan; et al.
Abstract: The formation of platelet ice is well known to occur under Antarctic sea ice, where subice platelet layers form from supercooled ice shelf water. In the Arctic, however, platelet ice formation has not been extensively observed, and its formation and morphology currently remain enigmatic. Here, we present the first comprehensive, long‐term in situ observations of a decimeter thick subice platelet layer under free‐drifting pack ice of the Central Arctic in winter. Observations carried out with a remotely operated underwater vehicle (ROV) during the midwinter leg of the MOSAiC drift expedition provide clear evidence of the growth of platelet ice layers from supercooled water present in the ocean mixed layer. This platelet formation takes place under all ice types present during the surveys. Oceanographic data from autonomous observing platforms lead us to the conclusion that platelet ice formation is a widespread but yet overlooked feature of Arctic winter sea ice growth. Plain Language Summary: Platelet ice is a particular type of ice that consists of decimeter sized thin ice plates that grow and collect on the underside of sea ice. It is most often related to Antarctic ice shelves and forms from supercooled water with a temperature below the local freezing point. Here we present the first comprehensive observation of platelet ice formation in freely drifting pack ice in the Arctic in winter during the international drift expedition MOSAiC. We investigate its occurrence under the ice with a remotely controlled underice diving robot. Measurements of water temperature from automatic measurement devices distributed around the central MOSAiC ice floe show that supercooled water and thus platelet ice occur widely in the winter Arctic. This way of ice formation in the Arctic has been overlooked during the last century, as direct observations under winter sea ice were not available and contrary to typical Antarctic observations; manifestation of platelet ice in Arctic ice core stratigraphy has been more challenging to identify. Key Points: Here we present extensive observations of platelet ice formation under Arctic winter sea ice The subice platelet layer appears to form locally due to seed crystals in ocean surface supercooling